Blood Metal Levels and Amyotrophic Lateral Sclerosis Risk: A Prospective Cohort. Issue 1 (6th November 2020) - Peters, Susan; Broberg, Karin; Gallo, Valentina; Levi, Michael; Kippler, Maria; Vineis, Paolo; Veldink, Jan; van den Berg, Leonard; Middleton, Lefkos; Travis, Ruth C.; Bergmann, Manuela M.; Palli, Domenico; et al.
Abstract : Objective: Metals have been suggested as a risk factor for amyotrophic lateral sclerosis (ALS), but only retrospective studies are available to date. We compared metal levels in prospectively collected blood samples from ALS patients and controls, to explore whether metals are associated with ALS mortality. Methods: A nested ALS case–control study was conducted within the prospective EPIC (European Prospective Investigation into Cancer and Nutrition) cohort. Cases were identified through death certificates. We analyzed metal levels in erythrocyte samples obtained at recruitment, as a biomarker for metal exposure from any source. Arsenic, cadmium, copper, lead, manganese, mercury, selenium, and zinc concentrations were measured by inductively coupled plasma–mass spectrometry. To estimate ALS risk, we applied conditional logistic regression models. Results: The study population comprised 107 cases (65% female) and 319 controls matched for age, sex, and study center. Median time between blood collection and ALS death was 8 years (range = 1–15). Comparing the highest with the lowest tertile, cadmium (odds ratio [OR] = 2.04, 95% confidence interval [CI] = 1.08–3.87) and lead (OR = 1.89, 95% CI = 0.97–3.67) concentrations suggest associations with increased ALS risk. Zinc was associated with a decreased risk (OR = 0.50, 95% CI = 0.27–0.94). Associations for cadmium and lead remained when limiting analyses to noncurrent smokers. Interpretation: This is the first study to compare metal levels before disease onset, minimizing reverse causation. The observed associations suggest that cadmium, lead, and zinc may play a role in ALS etiology. Cadmium and lead possibly act as intermediates on the pathway from smoking to ALS. ANN NEUROL 20209999:n/a–n/a